Współtworzenie znaczeń, czyli działania i strategie mediacyjne na zajęciach języka polskiego jako obcego z wykorzystaniem polskich tekstów literackich .......... 37 - Czerkies, Tamara; Banach, Małgorzata (Kultura i literatura w glottodydaktyce polonistycznej wobec wymagań rzeczywistości, 2025)
CO-CREATION OF MEANINGS, OR MEDIATION ACTIVITIES AND STRATEGIES IN JPJO CLASSES USING POLISH LITERARY TEXTSThe article discusses the issues of mediation and mediation activities that learners and teachers can undertake during classes of Polish as foreign language when literary texts are used. The first part presents the most important works of researchers and explains the basic concepts. In the practical part, it presents examples of how the assumed goals can be achieved by provoking students to specific actions when learners work with selected Polish literary texts.